Biomimetic nanoporous aerogels from branched aramid nanofibers combining high heat insulation and compressive strength. (8th February 2021) - Li, Jun; Li, Huaiyu; Xu, Liwei; Wang, Lijun; Hu, Zhen; Liu, Li; Huang, Yudong; Kotov, Nicholas A.
Abstract: Materials combining efficient thermal insulation and high mechanical properties are needed in many areas of technology. Various aerogels provide a convenient design framework for thermal insulators, but they are often brittle. Furthermore, the spectrum of advanced properties is constantly expanding while requirements to the degree of control of the three‐dimensional gel‐forming network is constantly increasing. Here, we report on biomimetic aramid nanofibers aerogels with the structure replicating articular cartilage, prepared by supercritical drying of 3D networks held together by hydrogen bonds. Owing to the branching morphology of the nanofibers, the three‐dimensional nanoscale networks with extensive percolation and high interconnectivity can be obtained. The aerogels showed high porosity with an average open pore size of 21.5 nm and correspondingly low specific density of 0.0081 g/cm 3 . The aerogels also possess a high compressive strength of 825 kPa at a strain of 80%. Due to the unique aramid chemistry of the parent nanofibers, aramid aerogels combine low thermal conductivity of 0.026 W/m·K with high thermal stability up to 530°C, which is unusually high for polymeric and composite materials of any type, opening a broad range of applications from electronics to space travel.